INFLUENTIAL DETERMINANTS SHAPING CONSUMER PURCHASING PATTERNS FOR ORGANIC FOOD PRODUCTS - Arora, Sheire; Jain, Aditi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study examines multiple variables that influence consumer’s purchasing behavior of organic products. This study incorporates both secondary and primary data. The main data is gathered via a standardized questionnaire. A total of 388 people from different areas of Jaipur city responded to the questionnaire.The study indicates a greater level of environmental awareness, a focus on the quality characteristics of organic products, and recognition of the health advantages associated with purchasing organic food products. Nevertheless, customers prioritize factors other than the price when it comes to organic foods. The research findings validate the correlation between consumer views and the inclination to purchase organic food products. The findings indicate that marketers can successfully develop marketing strategies by prioritizing aspects such as product quality, health advantages, and environmental friendliness, while considering pricing to a lesser extent, as these elements significantly influence customer attitudes and purchasing Patterns.